Medication overuse in oncology: current trends and future implications for patients and society. Issue 4 (April 2018) - Schleicher, Stephen M; Bach, Peter B; Matsoukas, Konstantina; Korenstein, Deborah
Summary: The high cost of cancer care worldwide is largely attributable to rising drugs prices. Despite their high costs and potential toxic effects, anticancer treatments could be subject to overuse, which is defined as the provision of medical services that are more likely to harm than to benefit a patient. We found 30 studies documenting medication overuse in cancer, which included 16 examples of supportive medication overuse and 17 examples of antineoplastic medication overuse in oncology. Few specific agents have been assessed, and no studies investigated overuse of the most toxic or expensive medications currently used in cancer treatment. Although financial, psychological, or physical harms of medication overuse in cancer could be substantial, there is little published evidence addressing these harms, so their magnitude is unclear. Further research is needed to better quantify medication overuse, understand its implications, and help protect patients and the health-care system from overuse.